Induction of Round Heart Disease in Turkey Poults by Feed Texture - Roberson, Kevin D. (International Journal of Poultry Science, 2005)
Incidence of round heart disease was prevalent in starting turkey poults in studies at our experimental facility. Two experiments were conducted to evaluate two dietary factors that may have contributed to increased susceptibility of poults to round heart disease. Experiment 1 consisted of 4 dietary treatments in which dietary chlorine ranged from 0.17 to 0.29% as a result of salt addition, but dietary sodium was maintained at 0.17%. Experiment 2 consisted of poults fed the same pre-starter (0-3 wk of age) and starter (3-6 wk of age) feeds. The diets were fed either in a mash or crumbled form with or without a post-hatch supplement the first day of the experiment. Poults were placed approximately 4 hr after departure from the hatchery. There was no evidence of round heart disease mortality in Experiment 1. According to body weight data, the dietary chlorine requirement was estimated to be 0.21% when adequate dietary sodium and potassium are fed. Mortality was increased in Experiment 2 due to round heart disease when crumbles were fed. The addition of a post-hatch supplement did not affect growth or mortality. The results of these studies indicate that feeding crumbles to poults increased round heart disease incidence starting at 6 days of age due to faster growth rate.